(3GdLhgQ GdefXhe hGdOQ GdefKhQ aj TQM OjhGf GdTPhQ aj GdCcSjQs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdMceI GdTQjaI cfRGddg JYGdi dcd hGQO eYdhe ai GdbSeI s
(3BNQgG (B:s
(3hEfeG cTafG Pdc EdG ddWGdH GdeSJMb EHJZGA dhLg Gddg JYGdi djNdU ef GdMQeGf hai Pdc eKhHg ef Gddg JYGdi QMeI ddWGdH GdUGOb hSGFQ GdENhGf s
(3TPhQ GdPgH dGHf CQaY QCS GfXQ cTa GdXfhf L(B2 (3U` (B1029s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs